The structural evolution of an ancient accretionary prism in the Damara Belt, Namibia - Hartnady, Michael Ian Hay (Department of Geological Sciences, 2015)
The Southern Marginal Zone (SMZ) of the Damara Belt, exposed in the Gaub Canyon in central Namibia, consists of fourteen lithotectonic units of high strain amphiholite facies rock with pelagic, hemi-pelagic and clastic sedimentary protoliths. These rocks are intercalated With lenses of metabasite. Regional high-pressure - low-temperature metamorphic conditions (~1O kbar and ~600°C) dominate the Southern and Southern Marginal Zones of the Damara Belt, leading to the interpretation that these tectonostratigraphic terranes formed in an accretionary prism along an ancient subduction margin. The structures in the SMZ are the result of progressive deformation, inferred to have initiated under low-grade metamorphic conditions (D₁) and evolved through prograde to peak metamorphism (D₂), ending in relatively low-temperature retrograde conditions (D₃). Each of the deformation phases is characterised by a foliation. D₁ is associated With pure shear dominated layer-parallel extension characterised by disrupted lithological layering and hedding-parallel foliation S₀+₁. D₃ is deﬁned as deformation related to the formation of an axial-planar S₂ caused by folding of S₀+₁ around F₂ hinge lines. Widespread isoclinal recumbent folding resulted in transposition of these fahrics and the general foliation is thus termed S₀+₁+₂. This composite foliation contains a down-dip stretching lineation L₂. Folding was contemporaneous With top-to-the-SE directed thrusting in D₂ faults and shear zones that are seen to displace D₁ fabric. Fold hinge lines parallel to L₂ suggest D₂ is characterised by non-ideal simple shear. D₃ is deﬁned by a crenulation cleavage S₃, at near right angles to S₀+₁+₂ foliation resulting from NW-SE pure shear shortening. This phase of deformation is also associated with retrograde, reverse faulting that is localised along some of the D₂ shear zones.